Evaluation of Virola oleifera activity in musculoskeletal pathologies: Inhibition of human multiple myeloma cells proliferation and combination therapy with dexamethasone or bortezomib. (23rd May 2021) - Francisco, Vera; Ruiz-Fernández, Clara; González-Rodríguez, María; Cordero-Barreal, Alfonso; Pino, Jesus; Viñuela, Juan E.; Lago, Francisca; Conde, Javier; Gómez, Rodolfo; Carvalho, Glaucimeire Rocha; Costa Pereira, Thiago Melo; Campos-Toimil, Manuel; et al.
Abstract: Ethnopharmacological relevance: Virola oleifera (Schott) A.C. Smith, Myristicaceae, has been widely used in traditional medicine in Brazil to treat rheumatic pain, joint tumours, skin diseases, halitosis, bronchial asthma, haemorrhoids, and intestinal worms. Recently, research data showed the antioxidant properties in several oxidative stress-related models. However, there is no experimental evidence supporting its potential use in managing rheumatic diseases and bone malignancies. Aims of the study: To evaluate the therapeutic potential of the resin from Virola oleifera in joint and bone diseases, namely arthritis, osteosarcoma, chondrosarcoma, and multiple myeloma. Materials and methods: To determine Virola oleifera resin (VO) effects on arthritis-associated inflammation and cartilage degradation, the LPS-induced NO production, and mRNA and protein expression of ADAMTS5, MMP13, COL2, and ACAN, were evaluated in chondrocytes (ATDC5 and TC28 cell lines). The cytotoxic effects of VO (0.05–50 μg/ml) on multiple myeloma (ARH-77), osteosarcoma (SAOS-2), and chondrosarcoma (SW-1353) cell lines were analysed by 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide (MTT) assay. The VO effects, combined with dexamethasone or bortezomib, were evaluated in a multiple myeloma cell line. The mechanisms of VO, alone or in combination with bortezomib, were determined by cell cycle analysis through flow cytometry, while expression levels of p-Akt/Akt, p-ERK/ERK, p-p38/p38 MAPK, Bax, Bcl-2, and cleaved-caspase-3/caspase-3 proteins by Western blot. Results: VO had no significant effect on LPS-induced NO production in chondrocytes at non-cytotoxic concentrations. VO treatment diminished the mRNA levels of metalloproteinases and ECM components; however, any significant effect was observed on the protein expression levels. The cell viability of a multiple myeloma cell line was strongly reduced by VO treatment in a dose- and time-dependent manner, while osteosarcoma and chondrosarcoma cell lines viability was significantly affected only by the highest dose assessed. In multiple myeloma cells, VO leads to G2/M cell cycle arrest. Furthermore, it synergizes with dexamethasone by increasing cell toxicity. Finally, VO reverts bortezomib activity by counteracting ERK1/2, Bax, and caspase-3 activation. Conclusions: The current work supports the ethnopharmacological use of Virola oleifera (Schott) A.C. Smith in bone and joint diseases, but there is no evidence for the amelioration of arthritis-associated inflammatory or catabolic processes. Our data also supports the potential use of Virola oleifera as adjuvant therapy to optimize the pharmacologic effects of current chemotherapeutic drugs. However, possible herb-drug interactions should be considered before clinical application. Graphical abstract: Image 1 Highlights: Therapeutic action of Virola oleifera resin (VO) in bone diseases was disclosed. No improvements in arthritis-associated inflammatory or catabolic processes. VO decreases multiple myeloma (MM) cell viability via G2/M cell cycle arrest. VO might be proposed as adjuvant therapy with dexamethasone in MM. Herb-drug interactions could limit combination therapy of VO with bortezomib.